The determination of the texture depth, skidding resistance and roughness index of various bituminous road surfaces [electronic resource] - 428829 Arafat Suleiman Yero; Fakulti Kejuruteraan Awam (2008)
Thesis (Sarjana Kejuruteraan (Awam - Pengangkutan dan Jalanraya)) - Universiti Teknologi Malaysia, 2008